Stop! Grammar time: University students’ perceptions of the automated feedback program Grammarly - ONeill, Ruth; Russell, Alex (Australasian Journal of Educational Technology, 2019)
Universities are increasingly looking towards online technology to assist their students. Grammarly advertises itself as the world’s most accurate online grammar checker, yet little research exists on its performance as a feedback tool in universities. This paper reports on a study investigating students’ perceptions of Grammarly when used in conjunction with advice from an academic learning advisor. Using a mixed methods sequential explanatory design, the study compared one group of students’ responses to the feedback they received from Grammarly (n = 54) with another group’s responses to the traditional non-automated grammar feedback they received from the Academic Learning Centre at CQUniversity (n = 42). Results show that students receiving feedback from Grammarly responded more positively to 9 of the 15 survey items and were significantly more satisfied with the grammar advice that they received compared with non-Grammarly students. No significant differences were registered between cohorts or delivery mode, which suggests that Grammarly can be used effectively by academic learning advisors to provide grammar support for both international and domestic students, online and on campus. It is recommended, however, that the program be used in conjunction with academic learning advisor input as the program is currently not accurate enough for independent use to be justified.